Dampak Pembangunan Jembatan Pelangi Terhadap Pemukiman Masyarakat - Patto; Sitti Kasmiati; La Ode Nursalam; Andrias (Jurnal Penelitian Pendidikan Geografi, 2024)
Before the Rainbow Bridge construction project, people were free to carry out activities to build embedded houses in residential locations. However, after the regional government program came into existence, community settlements began to be evicted and began to limit the expansion of residential locations, giving rise to pros and cons for the community on an ongoing basis. This research aims to determine the impact of the construction of the Rainbow Bridge on community settlements and determine the economic conditions of the community with the construction of the Rainbow Bridge. The method used in this research is qualitative descriptive research. The results of this research show that the rainbow bridge can encourage the socio-economic conditions of the community in a positive direction and indirectly improve economic conditions. The negative impacts caused have an impact on settlements as a place to live, limit community movement, and create opportunities for the people of Mola Nelayan Bakti Village to migrate to other areas.